Impact of Hyperuricemia on Incident Hypertension When Hypertension Definition Changes From 140/90 to 130/80 mmHg in a Large Taiwanese Population Follow‐Up Study - Yi‐Hsueh Liu; Wei‐Yu Su; Chih‐Yi Lin; Chun‐Chi Tsai; Ho‐Ming Su; Szu‐Chia Chen (The Journal of Clinical Hypertension)
ABSTRACT A lower blood pressure threshold (≥130/80 mmHg) to define hypertension has been proposed in several hypertension guidelines. This study assessed the relationship between hyperuricemia and incident hypertension, examining serum uric acid (SUA) cut‐offs using both traditional and new definitions in a large Taiwanese cohort. This observational cohort study enrolled 26 973 participants from the Taiwan Biobank (TWB), followed for a median of 4 years. Regarding traditional definition (140/90 mmHg), hyperuricemia (odds ratio [OR], 1.297), quartile 3 of SUA (OR, 1.211), quartile 4 of SUA (OR, 1.495), and high SUA (OR, 1.127) were significantly associated with incident hypertension in males, and hyperuricemia (OR, 1.198), quartile 4 of SUA (OR, 1.359), and high SUA (OR, 1.099) were significantly associated with incident hypertension in females. As for new definition (130/80 mmHg), hyperuricemia (OR, 1.376), quartile 3 of SUA (OR, 1.229), quartile 4 of SUA (OR, 1.554), and high SUA (OR, 1.139) were associated with incident hypertension in males, and hyperuricemia (OR, 1.249), quartile 3 of SUA (OR, 1.253), quartile 4 of SUA (OR, 1.429), and high SUA (OR, 1.096) were associated with incident hypertension in females. The interaction between hyperuricemia and sex on incident hypertension was significant for both traditional (140/90, p < 0.001) and new (130/80, p = 0.001) definitions. Hyperuricemia was significantly associated with incident hypertension under both traditional and new definitions. A significant interaction between hyperuricemia and sex was noted, although the differences were not so great.